Ancient Mitogenomes Provide New Insights into the Origin and Early Introduction of Chinese Domestic Donkeys - Wang, Linying; Sheng, Guilian; Preick, Michaela; Hu, Songmei; Deng, Tao; Taron, Ulrike H.; Barlow, Axel; Hu, Jiaming; Xiao, Bo; Sun, Guojiang; Song, Shiwen; Hou, Xindong; et al. (Frontiers in Genetics, 2021)
Both molecular data and archaeological evidence strongly support an African origin for the domestic donkey. Recent genetic studies further suggest that there were two distinct maternal lineages involved in its initial domestication. However, the exact introduction time and the dispersal process of domestic donkeys into ancient China are still unresolved. To address these questions, we retrieved three near-complete mitochondrial genomes from donkey specimens excavated from Gaoling County, Shaanxi Province and Linxia Basin, Gansu Province, China, dated at 2,349-2,301, 469-311 and 2,160-2,004 cal. BP, respectively. Maximum-likelihood and Bayesian phylogenetic analyses reveal that the two older samples fall into the two different main lineages (i.e., clade Ⅰ and clade Ⅱ) of the domestic donkey, suggesting that the two donkey maternal lineages had been introduced into Midwestern China at least at the opening of Silk Road (approximately the first century BC). Bayesian analysis shows that the split of the two donkey maternal lineages is dated at 0.323 Ma (95% CI: 0.583-0.191 Ma) using root-tip dating calibrations based on near-complete mitogenomes, supporting the hypothesis that modern domestic donkeys go back to at least two independent domestication events. Moreover, Bayesian skyline plot analyses indicate an apparent female population increase between 5,000 and 2,500 years ago for clade I followed by a stable population size to the present day. In contrast, clade II keeps a relatively stable population size over the past 5,000 years. Overall, our study provides new insights into the early domestication history of Chinese domestic donkeys.